Moronene Indigenous Recognition and Protection Regulation Hukaea Laea in Bombana County - Bakri Sulaiman; Abrar Saleng; Kahar Lahae (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
Regulations on the Recognition and Protection of Customary Law Communities are not always effective. This study was to determine the concept of recognition and protection of the Customary Law Community in Rawa Aopa Watumohai National Park. This research is a normative legal research. The results of the research are First, the law still provides conditional recognition of indigenous peoples, which limits their space. second, that the recognition and protection of the customary MHA of Moronene Hukaea Laea in Bombana Regency has not been maximized. They have received recognition and protection through a recognition of perda, but their customary territory still has the status of designating a National Park Area, so they cannot use it as customary land.